2015
DOI: 10.1089/ars.2014.6047
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial NADPH-Consuming Redox-Cyclers As Superior Glucose-6-Phosphate Dehydrogenase Deficiency Copycats

Abstract: Aims: Early phagocytosis of glucose-6-phosphate dehydrogenase (G6PD)-deficient erythrocytes parasitized by Plasmodium falciparum were shown to protect G6PD-deficient populations from severe malaria. Here, we investigated the mechanism of a novel antimalarial series, namely 3-[substituted-benzyl]-menadiones, to understand whether these NADPH-consuming redox-cyclers, which induce oxidative stress, mimic the natural protection of G6PD deficiency. Results: We demonstrated that the key benzoylmenadione metabolite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(104 citation statements)
references
References 60 publications
5
94
0
Order By: Relevance
“…We also showed that plasmodione specifically induces its toxic effects in parasitized erythrocytes without harming noninfected G6PD-sufficient or -deficient erythrocytes (11). The other drug activities referred to include the generation of drug metabolites acting on other targets, such as glutathione reductasecatalyzed redox cycling, methemoglobin reduction, iron(III) complexation, and inhibition of ␤-hematin formation, which are suggested to play a significant role in killing the parasite (11). It is noteworthy that in contrast to the structurally related antimalarial 1,4-naphthoquinone atovaquone, the lead benzylmenadione does not act as an inhibitor of the parasite's mitochondrial electron transport chain (8).…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…We also showed that plasmodione specifically induces its toxic effects in parasitized erythrocytes without harming noninfected G6PD-sufficient or -deficient erythrocytes (11). The other drug activities referred to include the generation of drug metabolites acting on other targets, such as glutathione reductasecatalyzed redox cycling, methemoglobin reduction, iron(III) complexation, and inhibition of ␤-hematin formation, which are suggested to play a significant role in killing the parasite (11). It is noteworthy that in contrast to the structurally related antimalarial 1,4-naphthoquinone atovaquone, the lead benzylmenadione does not act as an inhibitor of the parasite's mitochondrial electron transport chain (8).…”
mentioning
confidence: 68%
“…This deficiency stems from genetic mutations in the G6PD gene (12)(13)(14) resulting in reduced antioxidative capacities of erythrocytes and an early removal of Plasmodium-infected erythrocytes from the circulation. We recently demonstrated that among other activities, plasmodione mimics the natural protection of G6PD deficiency, marked by oxidative damage of P. falciparum-infected erythrocytes and their enhanced phagocytosis upon drug treatment (11). We also showed that plasmodione specifically induces its toxic effects in parasitized erythrocytes without harming noninfected G6PD-sufficient or -deficient erythrocytes (11).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…To achieve the radical treatment and elimination of Plasmodium parasites, especially Plasmodium falciparum, antimalarial drugs such as primaquine are required. These drugs act as oxidant and may lead to haemolysis in people with G6PD deficiency [6,19]. Therefore, knowledge about the prevalence of G6PD deficiency and other triggers of haemolysis for eradication of malaria is important.…”
Section: Introductionmentioning
confidence: 99%